Determinants of exacerbations in patients with chronic obstructive pulmonary disease: retrospective cohort study - Sihombing, Intan Ully Athalia; Pulungan, Rafiah Maharani; Karima, Ulya Qoulan; Pristya, Terry Y.R; Soetrisno, Arief Budi; Montain, Maya Marinda (Universitas Gadjah Mada, 2022)
Purpose: Exacerbations in patients with COPD are a significant cause of morbidity and mortality because of the increased progression of COPD, which is getting worse due to frequent recurrences. This study aimed to determine the factors associated with the incidence of exacerbations in patients with chronic obstructive pulmonary disease (COPD) at the Bandung Community Lung Health Center (BCLHC). Methods: This study is a secondary data analysis of patient medical records for 2015-2020 with a retrospective cohort study design. The sample in this study amounted to 122 COPD patients who were taken using a purposive sampling technique. The variables studied were age, sex, employment status, marital status, and smoking history. The bivariate data analysis used the chi-square test, and the multivariate data analysis used the multiple Cox regression test with α = 0.05. Results: The results of the multivariate analysis showed an increased risk of exacerbations in the group with a history of smoking (RR = 7.6, 95% CI = 2.9-19.6) compared to the group with no history of tobacco and non-married status (RR = 1.9, 95% CI = 1.1-3.4) compared with the currently married group. Conclusion: It is hoped that COPD sufferers can stop smoking to reduce the risk of exacerbations and the need for support from families for COPD sufferers who are not married.